FAKTOR-FAKTOR YANG MEMPENGARUHI FUNGSI PENGEMBANGAN SUMBER DAYA MANUSIA SDM - Victorynie, Irnie; Nujud, Ya’sub Atsyir; Rafa, Juana; Pasaribu, Muhammad Syafaruddin (Universitas Muhammadiyah Tapanuli Selatan, 2025)
A key component of building a flexible and fiercely competitive business is the role of human resource development (HRD). The purpose of this study is to describe several tactics that must be used when performing training and development of human resources, as well as to identify elements that influence HRD development in an organization. This study specifically seeks to ascertain (a.) The intent and purpose of having human resources (b.) A number of items pertaining to human resource development and training. The author's research methodology in this study is descriptive qualitative, and data is gathered through literature reviews that are collected from reliable websites, books, journals, interviews, and documents. The findings of this investigation The study's findings show that the interaction of internal and external factors has a significant impact on the success of HRD development. Among these, enhancing the caliber and potential of HRD requires strong leadership, dedication to training and growth, and flexibility in response to technology advancements. In addition to offering suggestions for stakeholders to foster an atmosphere that encourages expansion and creativity in HRD development, this study offers organizations valuable information for developing sustainable HRD development plans.